Ragam Makna Penafsiran Lafal Darran dan Naf’an Secara Berdampingan (Kajian Pengulangan Al-Qur’an) - Muhammad Najib; Muhammad Sayyidul Arwan (SALIHA: Jurnal Pendidikan & Agama Islam, 2020)
Darran (meanness) and naf'an (expediency) are two words that contradict in their meanings. In the Qur'an, both of them are sometimes used contiguously and are repeated in several places, in the same Surah or in different Suras. The focus of this study is the interpretation of Darran and naf’an contiguously in the Qur'an, analysis of the study of the repetition of the Qur'an. The interpretation method used in this study is the thematic method (maudhu’i). This method collects verses in which the Darran and Naf'an are pronunced contiguously, along with their explanations. Overall there are Darran and Naf'an that are pronounced contiguously, contained in 18 verses. Repetition of the pronunciation explains syirk behavior in various contexts as well as in a variety of different forms of pronunciation. In surah al-Baqarah verse 102, it explains the syirk behavior related to magic. Surat al-Maidah verse 76, describes the people who made the Prophet Jesus as worshipers. Surat al-An'am verse 71, Yunus verse 18, Taha verse 89, al-Anbiya ’verse 66, and ash-Syu’ara verse 73 explain about idolatry. Surat al-A'raf verse 188, Surah Yunus verse 49, and Surah al-Jin verse 21, describe the Prophet. who have no power, except for the will of God. Saba 'verse 42, describes the consequences received by the polytheists who will not get His blessing in the hereafter. The last, the Surah ar-Ra'd verse 16, al-Hajj verses 12-13, Jonah verse 106, al-Furqan verses 3 and 55, and al-Fath verse 11 explain about the actions of the polytheists broadly.